Analisis Sistem Pencegahan dan Penanggulangan Bahaya Kebakaran di Gedung Rektorat Universitas Nusa Cendana - JonsJonson H. Laning; Hari Rarindo; Dominggus G. Adoe; Rima N. Selan; Adi Y. Adoe (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2021)
To build a building, it is very important to pay attention to occupational health and safety (K3) for its residents. At the Nusa Cendana University Rectorate Building, the availability of a fire prevention and control system is very important. The purpose of this study was to analyze the extent of the fire prevention and control system in the Rectorate Building, University of Nusa Cendana. The fire hazard prevention systems analyzed are Fire Alarm, Fire Detector, Light Fire Extinguisher (APAR), Automatic Sprinklers, Fire Hydrants, Upright Pipe Systems, Water Supply Systems, Fire Pumps. The fire hazard management systems analyzed are the Fire Management Organization, Fire Emergency Action Procedures, and Fire Emergency Action Education and Training. The regulations that are used as a comparison with conditions in the field are the Minister of Public Works Regulation Number 26 / PRT / M / 2008, Number 20 / PRT / M / 2009, and NFPA (National Fire Protection Association) 10, 13, 14, 72, 101, 251. Based on the results of the analysis of the fire prevention and control system at the Rectorate Building of the University of Nusa Cendana, it is known that there are systems that are by accordance with the applicable regulations and there are also systems that are not by accordance with the applicable regulations. For this reason, the management of the Rectorate Building at the University of Nusa Cendana is advised to improve the existing fire prevention and control system so that it is by accordance with applicable regulations